Histology and Histochemistry of the Stomach Epithelium of Pachycondyla (= Neoponera) villosa (Formicidae: Ponerinae) - Baron, Noemi Carla [UNESP]; Bution, Murillo Lino [UNESP]; Pereira, Bruno Fiorelini [UNESP] (California State University, 2011)
In this work we carried out histological and histochemical analyses of the midgut of Pachycondyla (= Neoponera) villosa in order to study the generative cells (associated with epithelial regeneration) and goblet cells (associated with transport of ions through the epithelium). The regenerative cells are responsible for the replacement of the digestive cells and are grouped on the basis of these cells. The goblet cells are formed by a depression rich in microvilli through which secretion activity typically occurs.
Keywords: generative cells; goblet cells''; ventriculus; Pachycondyla